Imperialism In Africa - Augustus Fisher (Green Publisher Indonesia, 2022)
Since the phenomenon of Imperialism is so important for Africa’s political and economic thought, it is important to begin by understanding it. What is Imperialism? Imperialism cannot be defined in any generally acceptable way. It means different things to different people. Let us note some of these differences as they appear. Because the fruits of imperialism- the subordinate areas variously called possessions, colonies, protectorates, semi-protectorates, and dependent states- have long been regarded as valuable to the controlling state, they have been eagerly sought. Finally, we may ask, is it inherent in the very nature of underdevelopment that makes development such an impossible task? Among the many prescriptions, after “flag independence,” that have been offered- e.g. cultural, social, psychological, even economic-none has produced any encouraging results. In fact nearly all of them have had negative result, and made bad situations worse. Are we to continue with the same experiments at the expense of the people, who, have borne the whole burden of these experiments throughout the last decades this is the question to which all the developing countries, especially those in Africa, must address themselves